1994
DOI: 10.1002/ssu.2980100610
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic staging of prostatic carcinoma

Abstract: Current treatment of prostate cancer is highly controversial, however accurate assessment of pelvic lymph node status is important to determine early in the course of therapy if adjuvant hormonal ablation is necessary. Indications for laparoscopic assessment of pelvic lymph nodes are now better defined and the technique requires a high degree of technical skill and expertise. A series of 50 patients who underwent laparoscopic pelvic lymphadenectomy is presented. A greater than 40% chance of node positivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Most indications for pelvic lymphadenectomy are within the realm of urologic and gynecologic surgery. Several reports evaluating laparoscopic pelvic lymphadenectomy for staging prostate cancer have shown significant benefits, which include decreased pain, decreased hospital stay, and decreased use of laparotomy [46,47]. Laparoscopic pelvic and retroperitoneal lymphadenectomies have been used for staging other urologic tumors, such as bladder [48], penile [48,49], and non-seminomatous testicular cancers [50].…”
Section: Pelvic Lymphadenectomymentioning
confidence: 99%
“…Most indications for pelvic lymphadenectomy are within the realm of urologic and gynecologic surgery. Several reports evaluating laparoscopic pelvic lymphadenectomy for staging prostate cancer have shown significant benefits, which include decreased pain, decreased hospital stay, and decreased use of laparotomy [46,47]. Laparoscopic pelvic and retroperitoneal lymphadenectomies have been used for staging other urologic tumors, such as bladder [48], penile [48,49], and non-seminomatous testicular cancers [50].…”
Section: Pelvic Lymphadenectomymentioning
confidence: 99%
“…Several studies have attempted to define the low-risk, high-risk, or multiple-risk groups in an effort to guide clinician and patient in deciding the need for pretreatment nodal staging (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A summary of 12 of these studies is shown in Table 1.…”
Section: Defining the Risk Groupsmentioning
confidence: 99%
“…Most indications for pelvic lymphadenec‐tomy are within the realm of urologic and gynecologic surgery. Several reports evaluating laparoscopic pelvic lymphadenectomy for staging prostate cancer have shown significant benefits, which include decreased pain, decreased hospital stay, and decreased use of laparotomy 50,51 . Laparoscopic pelvic and retroperitoneal lymphadenectomies have been used for staging other urologic tumors, such as bladder, 52 penile, 52,53 and nonseminoma‐tous testicular cancers 54 …”
Section: Laparoscopy For Diagnosis and Staging Of Cancermentioning
confidence: 99%